2020
DOI: 10.3325/cmj.2020.61.450
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein gene family as biomarkers for recurrent prostate cancer

Abstract: Aim To assess kallikrein ( KLK ) expression in recurrent and non-recurrent prostate tumors and adjacent healthy prostate tissues. Methods The expression levels of 15 KLK genes in 34 recurrent and 36 non-recurrent prostate cancer samples and 19 adjacent healthy prostate tissue samples was assessed with quantitative reverse-transcription polymerase chain reaction. The samples were obtained from Baylor College of Medici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…In addition, KLK9 expression is low in all three cell lines. The role of KLK9 in prostate cancer is still unclear; it has only been shown that KLK9 expression was increased in recurrent tissue of prostate cancer patients (7). It is possible that KLK9 expression might be considered as a biomarker for analyzing tissues after treatment, but not suitable for early detection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KLK9 expression is low in all three cell lines. The role of KLK9 in prostate cancer is still unclear; it has only been shown that KLK9 expression was increased in recurrent tissue of prostate cancer patients (7). It is possible that KLK9 expression might be considered as a biomarker for analyzing tissues after treatment, but not suitable for early detection.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the other luminal subgroups, these cells highly express KLK4, which has been characterized as a potential biomarker for prostate, breast, and ovarian cancers. 5860 The regulation of KLK4 by androgens 61 and its function as a proliferative factor in the development of prostate cancer 62 suggest a possible role for this KLK4-high luminal subgroup in the promotion of prostatic enlargement. In addition, gene ontology analysis revealed a significant enrichment of established ribosomal gene sets in these KLK4-high cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cognizant of the usually long course of PCa, and the increasing prevalence of metastatic disease, as well as the high risk of local recurrence or progression to metastatic disease, and eventually death, despite initial definitive local treatment [ 1 , 2 , 3 ], it is of translational relevance that we found that a high PSA/AIM expression ratio is associated with enhanced metastability, and disease recurrence in patients with PCa, whereas, a high AIM/PSA ratio is associated with strong castration-induced regression ( Figure 3 and Figure 4 ). Concordant with these findings, in a recent study that prospectively evaluated six candidate biomarkers for detection of pelvic lymph node (LN) metastases (pN1) and prediction of BRFS in treated patients, while KLK2 and KLK3 outperformed the other predictive variables, and correctly classified all pN1 cases as molecular node-positive, KLK3 exhibited the highest concordance (96%) with histopathology for detection of LN metastases in the patients with PCa [ 22 , 23 ], and KLK3 protein expression was significantly enhanced in recurrent PCa tissues compared to the ‘normal’ tissues [ 24 ]. Moreover, Sugisawa et al [ 25 ] attributed the elimination of HCC cells to the AIM/CD5L produced by liver stellate macrophages/Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%